2017
DOI: 10.1101/202341
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A cell-free synthetic biochemistry platform for raspberry ketone production

Abstract: 22Cell-free synthetic biochemistry provides a green solution to replace traditional 23 petroleum or agricultural based methods for production of fine chemicals. 4-(4-24 hydroxyphenyl)-butan-2-one, also known as raspberry ketone, is the major fragrance 25 component of raspberry fruit and is utilised as a natural additive in the food and 26 sports industry. Current industrial processing standards involve chemical extraction 27with a yield of 1-4 mg per kilo of fruit. As such its market price can fluctuate up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…The Nicotiana tabacum L. DBR ( Nt DBR, UniProt ID: Q9SLN8) has been shown to be active toward a variety of α,β-unsaturated alkenes ( Mansell et al, 2013 ), such as (−)-cinnamaldehyde and 1-nitrocyclohexene. In addition, Rubus idaeus L. raspberry DBR ( Ri DBR, UniProt ID: G1FCG0) catalyzes the reduction of 4-hydroxybenzalacetone and 3-methoxy-4-hydroxybenzalacetone to raspberry ketone and zingerone, respectively ( Simon et al, 2017 ). A DBR from Malus domestica L. ( Md DBR, UniProt ID: A0A5N5GUE7) has been isolated and characterized recently ( Caliandro et al, 2021 ) and suggested to be involved in the biosynthesis of polyphenolic compounds (e.g., dihydrochalcones) that are beneficial in human diet.…”
Section: Introductionmentioning
confidence: 99%
“…The Nicotiana tabacum L. DBR ( Nt DBR, UniProt ID: Q9SLN8) has been shown to be active toward a variety of α,β-unsaturated alkenes ( Mansell et al, 2013 ), such as (−)-cinnamaldehyde and 1-nitrocyclohexene. In addition, Rubus idaeus L. raspberry DBR ( Ri DBR, UniProt ID: G1FCG0) catalyzes the reduction of 4-hydroxybenzalacetone and 3-methoxy-4-hydroxybenzalacetone to raspberry ketone and zingerone, respectively ( Simon et al, 2017 ). A DBR from Malus domestica L. ( Md DBR, UniProt ID: A0A5N5GUE7) has been isolated and characterized recently ( Caliandro et al, 2021 ) and suggested to be involved in the biosynthesis of polyphenolic compounds (e.g., dihydrochalcones) that are beneficial in human diet.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been emphasis on multi-enzyme complexes in cascades in the development of pathway engineering and it is clear that the rapid rise of synthetic biology owes much to the controllable cell-free environment, the ability to direct substrates toward the desired product and the facility with which superior combinations of often heterologous enzymes can be assembled. These issues have been reviewed in detail recently and the reader is referred to Jewett et al (2008); Carlson et al (2012), Gan and Jewett (2014), Hodgman and Jewett (2013), Jewett (2016, 2018), Kelwick et al (2016), Moore et al (2017b), and Silverman et al (2020). Further descriptions of pathway developments (for example, Dudley et al, 2019Dudley et al, , 2020 with limonene and isoprenoid synthesis).…”
Section: Prototypingmentioning
confidence: 99%
“…The PURE system relies on purified cellular components (108 in total, Shimizu et al, 2001) and is available commercially (New England Biolabs) but its high cost has prevented scale up. Its main use is in small scale prototyping (Moore et al, 2017b). A less expensive route is to employ crude cell lysates where the results are scalable into high volume fermentations (Zawada et al, 2011;Cai et al, 2015) coupled with inexpensive energy sources and an awareness of the problem of diversion of at least some of the target product into other reactions.…”
Section: Prototypingmentioning
confidence: 99%
“…These systems can also be an appropriate platform for production because of lower noise and toxicity and absence of resource competition between pathway and cell growth. To date, cell-free systems have been applied to implement pathways for violacein [49], 4-BDO [50], polyhydroxyalkanoates bioplastics [51], mevalonate [52], n-butanol [53] and raspberry ketone [54], using either transcriptiontranslation (TX-TL) systems, overexpressed enzymes in the crude extract or purified enzymes. Advantages and possibilities of cell-free systems for metabolic engineering has been reviewed elsewhere [55], and a methods chapter for pathway prototyping in cell-free systems has recently been published [56].…”
Section: Custom-made Biosensors' New Application Domain: Cell-free Mementioning
confidence: 99%